PEMBANGUNAN SISTEM AGRIBISNIS DI INDONESIA DAN PERANAN PUBLIC RELATION - BUNGARAN SARAGIH (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
Mistook of economic development strategy in lastime and economic crisis prolongedwith various its excess, to compel Indonesia choice alternative strategy in development ofeconomic, which hoped able to give solution of existing problems, without appear newproblems. Among some economic development strategy which fulfill the some conditions isAgribusiness Led Development, namely a strategy of economic development which integratedevelopment of agriculture (include estate crop, animal husbandry, fishery, and forestry) withdevelopment of agro-industry and linkage services setors. Development strategy ofagribusiness system to be convinced able to lead Indonesia economy has competitiveness andsinergys in the world economy.To develop the agribusiness system competitiveness, people-driven, sustainable anddecentralized are resposible all of agribusiness stake-holder, suitable with each role. Theentreprise is main actors of development agribusiness, the government have a role asfacilitator, regulator and promotor of agribusiness development, the researcher have a role todevelop of technology, education have a role to increase skill of human resources.Meanwhile, public relation profession have a role to build public good image, fordevelopment of agribusiness as well as for firm and agribusiness products.Special about the role of public relation (PR) in development of agribusiness system inIndonesia untill now still not develop yet. Whereas, PR functions very needed in developmentof agribusiness system, start from macro level till micro level. At macro level, role of PRhoped able to develop good image about importance to develop agribusiness in nationaleconomic development.